Sublime Self-Fashioning in Goytisolo’s “Reivindicación del conde don Julián” - Stallings, Gregory C. (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
My study attempts to assess the importance of Goytisolo’s novel for the contemporary reader. Recent studies of Conde Julián have found its violence toward women incongruous with our contemporary climate of sensitivity. Instead of concentrating on aspects of the novel that made it of such interest as a response to Franco’s fascism at the time of its publication (intertextuality, theoretical influences, mythic elements, political or literary satire, etc.), the present study examines the novel according to several complementary theoretical concerns receiving much attention of late: self-fashioning, testimony, and fetishism—themes that all in one way or another touch on the sublime. The first half of the paper uses Jean-Francois Lyotard’s concepts of testimony to show how the narrator fashions a rather unstable identity out of the void of his own non-existence (he is a non-identity under Franco’s regime). The latter half relies heavily on Walter Benjamin’s concept of the fetishistic gaze in order to suggest that the novel’s violent episodes may be read allegorically; they represent new forms of art related to mechanical production (and the fetishism of commodity consumerism) that subvert Western mimetic art forms. The essay concludes by affirming the narrator’s subversive role as Benjamin’s dialectical image; he ultimately creates a space apart from symbolic order wherein oppressed voices will no longer be silenced.